Policy Networks, the Third Sector and the Movements to Privatize Brazilian Education - Úrsula Adelaide de Lélis; Leonice Matilde Richter; Vilma Aparecida de Souza; Wane Elayne Soares Eulálio (Universidade Federal do Norte do Tocantins, 2020)
As a strategy to develop education for productivity, to legitimize the most recent configuration of capitalism, to guarantee the position of the hegemonic-ruling class and to promote the pedagogical market, business groups have organized movements that have assumed a leading role in the definition of educational public policies. When composing a third sector, they develop partnerships that leave the borders between public and private thinner and assume certain functions of the State. This performance maintains organic relations with international companies through policy networks. The aim of this study was to analyze the incidence of the third sector, public-private relations and policy networks in the Brazilian public education. Through the theoretical-documental study, with a quantitative and qualitative approach, the All for Education and the Base Movement were cut out. Analyses show that these movements have marked the transposition of the ideals and actions of the business community to public education, legitimized by partnerships with institutions, governments and the State. Focusing on educational policies, they act as mechanisms for privatization and increased profits, reorienting educational management. The importance of movements and associations for the defense of secular, public and socio-political education endorsed is underlined to challenge and restrain public-private actions in the definition of public educational policies.